The effect of productive learning outcomes, social circumstances, economic conditions, and creativity toward entrepreneur interest among fashion department students in vocational high school - Mohammad Adam Jerusalem; Triyanto Triyanto; Nur Kholifah; Miladiah Susanti; Ratna Utami Ningsih; Sylvia Martha Aprilia Silaen (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
The objectives of this research are to know the effect of productive learning, social situation, economic situation, and creativity towards the interest in entrepreneurship for students of class XII of Clothing Vocational Schools in Yogyakarta in 2018/2019. The method in this study is a correlational method with a quantitative approach. The population of this study were students of class XII of the Clothing Vocational School in Yogyakarta City, totaling 265 students. The number of research samples is 152 students with a sampling technique of proportional random sampling. Data collection techniques were questionnaires and documentation. The results of this study show that the learning outcomes of productive, social situation, economic situation, and creativity subjects affect the interest in entrepreneurship for the SMK students in the city of Yogyakarta.